A taxonomic revision of South American species of the seed-harvester ant genus Pogonomyrmex (Hymenoptera: Formicidae). Part II - Johnson, Robert A. (Zootaxa, 2021)
This paper provides a taxonomic revision and reviews natural history for 35 South American species of the seed-harvesting ant genus Pogonomyrmex. Species treated herein mostly comprise the P. rastratus-group; four species are revived from synonomy, three taxa are elevated from subspecies to species, five taxa are synonymized, and 20 new species are described. The following taxa are revived from synonomy: P. intermedia Menozzi, P. semistriata Emery, P. spinolae Emery, and P. weiseri Santschi. The following taxa are raised from subspecies to species: P. leonis Kusnezov, P. pulchellus Santschi, and P. sanmartini Kusnezov. The following new synonymies are proposed, with the senior synonym listed first, and the junior synonym(s) in parentheses: P. carbonarius Mayr (= P. kusnezovi Cuezzo & Claver, = P. weiseri var. neuquensis Santschi, = P. variabilis Santschi); P. vermiculatus Emery (= P. vermiculatus var. chubutensis Forel, = P. vermiculatus var. jorgenseni Forel). The following new species are described: P. apterogenos, P. araucania, P. atacama, P. bolivianus, P. colca, P. cusquena, P. excelsior, P. forelii, P. granulatus, P. lagunabravensis, P. loaensis, P. mapuche, P. maulensis, P. pichachen, P. propinqua, P. santschii, P. strioligaster, P. tafi, P. varicolor, and P. wilsoni. One species treated herein has brachypterous queens (P. atacama), one species has dimorphic queens (winged and brachypterous in P. longibarbis), and two species have ergatoid (permanently wingless) queens and ergatoid males (P. apterogenos, P. laguanbravensis); the latter two are the only known ant species in which both sexual castes are only ergatoid. I also provide keys for workers and queens (in English and Spanish), diagnoses for males, photographs of known castes, distribution maps, and a summary of known biology.